2009
DOI: 10.4018/jegr.2009092202
|View full text |Cite
|
Sign up to set email alerts
|

Quality Enhancing the Continued Use of E-Government Web Sites

Abstract: This study empirically examines Web site quality toward the enhancement of the continued use of e-government Web sites by citizens. The web site quality under examination includes three main aspects, which are information quality, system quality, and service quality. The participants were 614 country-wide e-citizens of Thailand. The data were collected by means of a web-based survey and analyzed by using multiple regression analysis. The findings revealed that the three quality aspects enhanced the continued u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 34 publications
6
50
0
3
Order By: Relevance
“…Initial use of egovernment Web sites is an important indicator of e-government success. Some information system research indicated that its eventual success depends on its continued use rather than firsttime use [17,28,29]. However, the desired outcome is not achieved unless a significant number of citizens move beyond the initial adoption and use e-government web sites on a persistent basis [17].…”
Section: Discussion: E-government Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial use of egovernment Web sites is an important indicator of e-government success. Some information system research indicated that its eventual success depends on its continued use rather than firsttime use [17,28,29]. However, the desired outcome is not achieved unless a significant number of citizens move beyond the initial adoption and use e-government web sites on a persistent basis [17].…”
Section: Discussion: E-government Challengesmentioning
confidence: 99%
“…Some information system research indicated that its eventual success depends on its continued use rather than firsttime use [17,28,29]. However, the desired outcome is not achieved unless a significant number of citizens move beyond the initial adoption and use e-government web sites on a persistent basis [17]. According to case studies from different countries, there are many challenges and issues that need to be addressed for successful implementation of e-government.…”
Section: Discussion: E-government Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kearns study, for example, evaluates effective delivery of public service through the lens of public value but does not consider the quality of e-government systems attributes like usability, functionality or information [30]. The other frameworks that are generally extensions of this original work, inherit the problem of insufficient attributes for evaluating systems quality.…”
Section: Evaluation Framework Based On Public Value Theorymentioning
confidence: 99%
“…user satisfaction)? Various studies [2,9,10] argue for the importance of usability in eGovernment environments. Usability is a part of the field of humancomputer interaction (HCI) which is the discipline concerned with design development, assessment and implementation of interactive systems for human use [11].…”
Section: Related Workmentioning
confidence: 99%